(untitled) (The Pakistan Development Review, 2014)
Acute shortage of energy sources in developing countries in general and South Asian countries in particular has shown that energy has become a binding input for any production process. Nowadays operation of heavy machinery and electrical equipment, and transportation of raw material and final products from their place of origination to their destination require heavy consumption of energy in one form or the other. Therefore, energy consumption that was previously ignored in the production function of a firm and an economy is now considered a vital input in production process. It affects GDP directly as by increasing energy consumption; more output can be produced with given stock of capital and labor force in a country. Also uninterrupted availability of energy at reasonable cost improves competiveness of home products in international markets and thus increases exports of home country a great deal. Resulting increase in net exports further adds to the GDP through multiplier effect